Single photon emission computed tomography in long-term survivors of adult brain tumours. Issue 6 (June 1994) - Ebmeier, K P; Booker, K; Gregor, A; Cull, A; Dougall, N; Sellar, R; Goodwin, G M
Abstract : Sixteen patients with primary brain tumours were examined on average eight years after treatment with surgery or whole brain irradiation using standard clinical assessment, CT, a neuropsychological test battery, and single photon emission CT (SPECT) with 99mTc-exametazime. Seventeen lesions were discovered on inspection of SPECT images, 11 with x-ray CT. Quantitative assessment of tracer uptake compared with 16 matched healthy volunteers was consistent with the presence of lesions. Measurement of uptake in brain regions of the hemisphere not containing the primary tumour still showed significant reductions in patients. This may be due to remote direct effects of the tumour or, more likely, to the whole brain irradiation received. Psychometric performance on most tests was significantly impaired in the patient group and was correlated with abnormalities of tracer uptake to relevant brain regions.